SAT0285 Characteristics of MPO-ANCA Positive Granulomatosis with Polyangitis. (10th June 2014) - Ono, N.; Ueda, A.; Uezono, S.; Himeji, D.; Sawabe, T.; Yoshizawa, S.; Yoshizawa, S.; Nishizaka, H.; Furugo, I.; Kiyohara, C.; Tada, Y.; Horiuchi, T.
Abstract : Objectives: Through the investigation of the actual situation of ANCA associated vasculitis in Japan, we attempted to clarify the characteristics of MPO-ANCA positive Granulomatosis with polyangitis (MPO-GPA). Methods: Retrospectively we recruited 38 GPA cases from 8 hospitals, and 41 Microscopic polyangitis (MPA) cases from one hospital. To exclude diagnostic overlaps, GPA and MPA were classified by EMA classification. Their clinical courses were analyzed based on sex, age, ANCA, organ involvements and treatment outcomes. Results: The mean age of GPA and MPA were 64.9 and 72.3 years old respectively. Among GPA, 15 cases (39%) were positive for PR3-ANCA, 17 (45%) cases were positive for MPO-ANCA, and 6 cases (16%) were ANCA negative. All MPA were MPO-ANCA positive. The mean ages are 60.4, 69.6, 63.0 and 72.3 years old respectively. The ratios of female are 20%, 82%, 50% and 56%. Compared to PR3-ANCA positive GPA (PR3-GPA), MPO-GPA had more otitis media, less arthritis, lower serum creatinine levels and more neuronal involvement. Compared to MPA, MPO-GPA had significantly more ENT involvements, pulmonary involvements and lower creatinine level. Both GPAs experienced more relapses than MPA. MPA showed significantly poor outcome than GPA (p=0.008). The mortality rates of GPA and MPA were 5% (mean follow-up time 1576 days) and 24.4% (mean follow-up time 778.2 days). MPO-GPA showed significantly fairer outcome than MPA even though their higher age (p=0.013). The univariate analysis selected following factors as predictors of a poor outcome: pulmonary UIP pattern (P=0.001), Cr1.7mg/dl (p=0.005), absence of ENT involvement (p=0.032), higher age (65 years old, p=0.062) and pulmonary hemorrhage (p=0.081). Conclusions: MPO-GPA is characterized by older female patients with otitis media, neuronal involvement and less renal injuries. Like PR3-GPA, MPO-GPA showed fairer treatment outcome but more relapse than MPA. Because of their higher age and fairer outcome, we need to manage MPO-GPA differently from PR3-GPA and MPA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1283